Assessment of Long-Term Socio-Geo-Ecological Consequences of Lead-Zinc Ore Mining on Vaygach Island - Igor V. Miskevich; Ekaterina I. Kotova (Арктика и Север)
The article evaluates possible negative geo-ecological consequences for the inhabitants of Varnek settlement from the development of polymetallic ore deposit in the southwest of Vaygach Island in the first half of the 20th century. Accumulation of heavy metals in algae of lagoonal estuaries of the Krasnaya (control site) and Varkutsyakha (background site) rivers was considered. There is an abandoned lead-zinc ore mine on the watershed of the Krasnaya River, where dumps of lead-zinc ore were left. The data were obtained that in the mouth of this river there is a significant accumulation of heavy metals in filamentous algae and fucus compared to the background site. At the same time, the content of lead in algae of the control site exceeding the permissible sanitary norm by 4.8 times was recorded. It is assumed that when waterfowl and fish use algae as food (through zooplankton and zoobenthos), lead in excessive concentrations may enter the organisms of local Nenets, for whom fishing and hunting have become the main occupation in the conditions of observed unemployment. To prevent possible negative effects of polymetallic ore mining on the human body, recommendations are given on what areas on the island should be avoided when setting up stations and bases for activities within the framework of the Vaygach State Nature Reserve and for tourism development.